Direct Preparation of Alginate Oligosaccharides from Brown Algae by an Algae-Decomposing Alginate Lyase AlyP18 from the Marine Bacterium Pseudoalteromonas agarivorans A3 - Xiao-Hui Sun; Xiao-Dong Zhang; Xin-Ru Zhang; Xiao-Fei Wang; Xi-Ying Zhang; Yu-Zhong Zhang; Yu-Qiang Zhang; Fei Xu (Marine Drugs)
Alginate oligosaccharides (AOs), derived from alginate degradation, exhibit diverse biological activities and hold significant promise in various fields. The enzymatic preparation of AOs relies on alginate lyases, which offers distinct advantages. In contrast to the conventional use of sodium alginate derived from brown algae as the substrate for the enzymatic preparation of AOs, AO preparation directly from brown algae is more appealing due to its time and energy efficiency. Thus, the identification of potent alginate lyases and cost-effective brown algae substrates is crucial for optimizing AO production. Herein, we identified and characterized an alginate lyase, AlyP18, capable of efficiently decomposing algae, from a marine bacterium Pseudoalteromonas agarivorans A3 based on secretome analysis. AlyP18 is a mesothermal, endo-type and bifunctional alginate lyase with high enzymatic activity. Two brown algae substrates, Laminaria japonica roots and Macrocystis pyrifera, were used for the AO preparation by AlyP18. Upon optimization of AlyP18 hydrolysis parameters, the substrate degradation efficiency and AO production reached 53% and ~32% for L. japonica roots, respectively, and 77% and ~46.5% for M. pyrifera. The generated AOs primarily consisted of dimers to pentamers, with trimers and tetramers being dominant. This study provides an efficient alginate lyase and alternative brown algal feedstock for the bioconversion of high-value AOs from brown algae.